Analysis of Implementation of Electronic Medical Record at the Outpatient Unit of Poso Regional General Hospital - Poniman Poniman; Munir Salham; Hamidah Hamidah (Universitas Ibn Khaldun Bogor, 2026)
Electronic Medical Records (EMR) are an important part of the digital transformation of healthcare services, aimed at improving efficiency, service quality, and patient safety. The implementation of EMR in healthcare facilities continues to evolve; however, in practice, various obstacles remain, both technical and related to user acceptance. Therefore, an analysis of user perceptions is required to determine the level of acceptance of the EMR system in healthcare services. This study aims to analyse the implementation of Electronic Medical Records (EMR) at the Outpatient Installation of Poso Regional General Hospital based on perceptions of ease of use, usefulness, and behavioural intention to use. This research employs a qualitative approach with a case study method. The informants in this study totalled six people, consisting of doctors, nurses, midwives, pharmaceutical staff, admission officers, and the head of the outpatient installation. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that, in terms of ease of use, EMR is generally easy to use in service delivery, although there are still technical obstacles, such as network issues and initial system understanding. From a usefulness perspective, EMR helps improve service efficiency, accelerates data access, and supports service quality. From the aspect of behavioural intention, healthcare workers show a tendency to continue using EMR and are willing to recommend its use, although improvements to the system and infrastructure are still needed. This study concludes that the implementation of EMR at the Outpatient Installation of Poso Regional General Hospital has provided ease of use and benefits in service delivery and is supported by healthcare workers’ intention to use it; however, strengthening of technical aspects and the system is still required to support more optimal use.